Model Fisik Redaman Energi Gelombang Dengan Breakwater Tiang - Juventus Welly Ginting; Ida Ayu Irawati Diah Ratna Putra; Eduardo Meyrianso Simanjuntak (JURNAL TEKNIK HIDRAULIK, 2019)
Breakwaters is one of type coastal structure that is mainly used as part for coastal protection purposes. Among the various types of breakwaters, likely rigid and hollow vertical pole types are one of the alternative structures for coastal protection. The utilization of this structure usually in the port area or in marina which protrudes into the sea. The pile breakwater test was carried out at laboratory experimental station for coastal engineering Buleleng Bali, on a scale of 1:10. This trial was carried out using pile materials using PVC pipes with a diameter of 6 cm. Scaling of this model is based on the piles used in the project sea dike stage A-NCICD. In testing this physical model several variations were carried out such as tata letak variation (N), wave height (h), wave period (t), distance between piles (columns) relative to diameter (B/D), and distance between piles (row) relative to diameter (b / D). Based on the test results obtained the optimal stacking configuration to reduce wave energy is a configuration with pole configuration B / D = 1; b / D = 0.5